Biostimulation of Indigenous Fungi with Agung Banana Semeru Lumajang Peel Extract in Reducing Ammonia Levels - Dwi Nur Rikhma Sari (Journal of Biotropical Research and Nature Technology, 2024)
Indonesia is the second rubber producer in the world, in its processing rubber produces liquid waste that contains quite high ammonia levels. This study aims to provide an alternative solution to the problem of water pollution due to ammonia in rubber industry liquid waste using a bioremediation process with a simple bioreactor. This study used indigenous fungi treatment of 4% and banana peel extract of 0%, 5%, and 10%. This study studies the potential of indigenous fungi with banana peel extract nutrients to reduce ammonia levels in water. The parameter measured is the level of ammonia in the water in the bioreactor. The results showed that indigenous fungi with banana peel extract nutrients had an effect on ammonia parameters. Treatment with a concentration of indigenous fungi 4% and banana peel extract 10% had a significant effect on reducing ammonia levels. The more indigenous fungi inoculum and banana extract used, the more effective it is in reducing ammonia in water.